2016
DOI: 10.5653/cerm.2016.43.4.240
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intrauterine instillation of granulocyte colony-stimulating factor in infertile women with a thin endometrium: A pilot study

Abstract: ObjectiveThe study aimed to investigate the efficacy of intrauterine instillation of granulocyte colony-stimulating factor (G-CSF) on the day of ovulation triggering or oocyte retrieval in infertile women with a thin endometrium.MethodsFifty women whose endometrial thickness (EMT) was ≤8 mm at the time of triggering during at least one previous in vitro fertilization (IVF) cycle and an index IVF cycle were selected. On the day of triggering (n=12) or oocyte retrieval (n=38), 300 µg of G-CSF was instilled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
2
7
0
1
Order By: Relevance
“…It starts with the apposition of the blastocyst at the uterine endometrium and then attachment to the endometrial surface epithelium . Several studies have shown that a thin endometrium adversely affects the pregnancy rate in IVF …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It starts with the apposition of the blastocyst at the uterine endometrium and then attachment to the endometrial surface epithelium . Several studies have shown that a thin endometrium adversely affects the pregnancy rate in IVF …”
Section: Discussionmentioning
confidence: 99%
“…9 Several studies have shown that a thin endometrium adversely affects the pregnancy rate in IVF. [10][11][12] After surgical abortion, inflammation can occur in both the endometrium and the oviduct. Endometritis is chronic inflammation of the inner lining of the uterine cavity, and leads to abnormal uterine bleeding, recurrent spontaneous abortion, and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…After intrauterine G-CSF treatment, the endometrial lining significantly increased in the cohort, with 3/12 (20%) patients subsequently conceiving [30]. Most recently, Lee and colleagues also demonstrated that intrauterine G-CSF (300 μg) on either trigger day or retrieval day significantly increased the EMT in patients with thin lining, resulting in pregnancy rate of 22.0% [31]. Interestingly, there was a trend for higher implantation, clinical pregnancy, and ongoing pregnancy rates when the G-CSF was instilled on the day of HCG trigger vs. day of egg retrieval [31].…”
Section: Results (Summarized Inmentioning
confidence: 99%
“…Several studies with different results have assessed the effect of G-CSF on endometrial thickness and IVF success [16,17]. In the studies of N. Gleicher et al [18]and Dayong Lee et al [19], the endometrial thickness, implantation and pregnancy rates were signi cantly higher in IVF patients treated with G-CSF, whereas in the studies of Eftekhar M et al [20] and Shivani Jain et al [21], treatment with G-CSF did not affect endometrial thickness and pregnancy outcomes in IVF patients. This difference may be related to the inconsistent with selection criteria of patients.…”
Section: Introductionmentioning
confidence: 99%